A Pragmatic Study of Bullying in “An American Girl: Chrissa Stands Strong” Movie - Mahdi, Duaa Abd Al-Haleem; Burhanuddin, Israa (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
This study explores the phenomenon of bullying as a prominent sociocultural element within the American film